JEL Classification System (Journal of Economic Literature, 2020)
The categories listed below are used to classify books, book reviews, journal articles, and dissertations indexed in JEL, JEL on CD, EconLit. New changes to the classification system appear as soon as possible on www.econlit.org . The JEL classification system may be used freely for scholarly purposes. We suggest the following format: “JEL: A10, B10, etc.”